Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas, dan Reputasi KAP terhadap Audit Delay - Maylansri, Roro Ayu; Andayani, Wuryan (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2022)
This study aims to examine the effect of company size, profitability, solvability, and public accounting firm reputation on audit delay. This study involves secondary data obtained from the company’s official website, www.idx.co.id. The samples include 38 trade, service, and investment companies listed on the Indonesia Stock Exchange from 2018 to 2020 selected through the purposive sampling method. The results of the multiple regression analysis indicated that profitability with the proxy of return on assets (ROA), solvability with the proxy of debt to assets ratio (DAR), and audit firm reputation had a significant negative effect on audit delay. Whilst, company size with the proxy of the natural logarithm of the total assets had no effect on audit delay.